Effect of Water Loading on the Chemical Structure and Mechanical Properties of Thermoplastic Tapioca Starch Film - Adamu, Ajiya Dahiru; Jikan, Suzi Salwah; Hj. A. Talip, Balkis; Badarulzaman, Nur Azam; Matias-Peralta, Hazel Monica; Derawi, Darfizzi; Yahaya, Shehu (International Journal of Integrated Engineering, 2020)
The effect of water (as a primary plasticiser) content on the chemical structure and mechanical properties of thermoplastic tapioca starch (TPTS) film was evaluated. The TPTS films were produced by tape casting technique through mixtures of fixed amount of glycerol and varied contents of tapioca starch and water. There was observed increase in hydrogen bonding interaction between starch and water molecules depicted by the downward shift between 3303-3281 cm-1. The excessive amount of water loading portrayed increase in crystallinity due to free volume movement of the starch particles. The changes in water loading also showed variation in the tensile strength and elongation at break of the TPTS films. This observation is because of the dependence of mobility of polysaccharide plastics on the water content in the premix. Therefore, starch forms entanglements with the plasticisers to form a flexible film.